EWC660: English for Proposal Writing / Academy of Language Studies - UiTM, Academy of Language Studies (2023)
This course is designed to develop students’ ability to write proposals. It focuses on exposing students to the basic parts of a proposal and developing their ability to use appropriate format and language for a proposal.